If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(4 + -4) = 9x + -33 Combine like terms: 4 + -4 = 0 9(0) = 9x + -33 Multiply 9 * 0 0 = 9x + -33 Anything times zero is zero. 0 = 9x + -33 Reorder the terms: 0 = -33 + 9x Solving 0 = -33 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 0 + -9x = -33 + 9x + -9x Remove the zero: -9x = -33 + 9x + -9x Combine like terms: 9x + -9x = 0 -9x = -33 + 0 -9x = -33 Divide each side by '-9'. x = 3.666666667 Simplifying x = 3.666666667
| 8(3s+5)=352 | | -42m-15=57 | | 2(2y+7)=18 | | 3(2l+9)=93 | | (2x/3y)x(9y/4x^2) | | tan=1.7 | | 2g+2u=q | | 11-2x+4=8+4x | | (13/52)*(12/52) | | X/-6=-9 | | 3(12+6r)= | | 6(3r+5)+1= | | 25x^6-49b^2=0 | | x*x*x=-27 | | -x+18=4 | | -2(x+1)=-22 | | (5w-3y+4)(7w+1)=0 | | 7x+33=9x+7 | | 8p-16=4p+32 | | 5+109875432=+13689765 | | 8x+4=3x+6 | | 5*+10987655321= | | 3x+5=27x-1 | | 1-3(2m-7)=4 | | -5(x-1)=3x+1-4x | | 32+90+x=180 | | 5/9(-13-32) | | 2x^3+4x^2+4x=-5 | | 4x-32+5x+45=36 | | 2-5m+7=8+2m | | 2x^3+4x^2+4x+5=0 | | 4x-2x=4x-2 |